Effectiveness of the career calm booklet in increasing self-efficacy and reducing anxiety - Evellyn Aiko Christiani; Gabriella Nydia Rahardja; Lyra Fiorentina Subianto; Kuncoro Dewi Rahmawati (Faculty of Psychology Universitas Islam Sultan Agung Semarang, 2026)
Final-year students often experience career anxiety due to pressure in planning their future. Self-efficacy plays a crucial role in reducing such anxiety, yet effective self-help interventions remain limited. This study aims to examine the effectiveness of the booklet “Career Calm: 30 Days to Improve Your Self-Efficacy” in increasing self-efficacy and reducing career anxiety. The research employed a one-group pretest-posttest design with a quantitative quasi-experimental approach. Thirty final-year university students in Surabaya experiencing career anxiety participated in a 30-day intervention. Results from the paired sample t-test showed a significant increase in self-efficacy and a decrease in career anxiety after the intervention (p < 0.001). However, correlation analysis revealed no significant relationship between the two variables. These findings suggest the booklet is effective independently, though other mediating variables such as motivation or hope may influence the relationship. The booklet has potential as a self-help intervention tool in career counseling programs.